Analyzing the Odds Ratio Via Distribution Function - Gurcan, Mehmet; Kaya, Mehmet Onur; Gural, Yunus (Bezmialem Vakif Univ, 2021)
Objective: The use of cross tables was frequently seen in early literature research in the biostatistics. Furthermore, its importance in many clinical examinations is still evident today. The aim of this study is to investigate how the 2x2 type tables are perceived in probability literature and how some studies are applied in practice. Thus, different methods can be developed for the purposes of applications. Methods: The method used to determine the distribution of a 2x2 type table is to consider one cell of a table as a random variable and calculate the probability that this variable can take the observed value. Hypergeometric distribution was taken into consideration in the study. This issue is explained in the methodology section of the study. Results: Some of the important statistics obtained from 2x2 type tables are the numerical statistical values that direct the researcher in experimental studies such as odds ratio. Considering the distribution of the table, the probabilities of these values are a very important finding for the experimental study. In particular, a high probability value is a measure of how well the statistical value commonly used in biostatistics applications, such as the odds ratio, represents the experimental study performed. Conclusion: According to the findings of the study, one of the observed results is the determination of the maximum probability ratio representing the experimental study, and the other is the weighted odds ratios that are used to combine odds ratios in the meta-analysis.
Keywords: Contingency table; probability distribution; hypergeometric distribution; odds ratio; relative risk; meta-analysis